An archaeological foundation to soil sustainability - Graham, Elizabeth; Evans, Daniel L.; Macphail, Richard; Stegemann, Julia; Glanville-Wallis, Francesca (Equinox Publishing, 2023)
Diverging from traditional archaeology, our ongoing research focuses on decomposition rather than preserved fragments of what people left behind. We are looking at the bulk of what constitutes archaeological deposits: soil. Comparing the thickness of soil where people have lived to thickness where there has been no human occupation shows greater accumulation, or soil formation, where humans have been active. These same soils are also often characterised by higher fertility than soils formed in the absence of humans. The implication is that the decay of what people throw away, leave behind or bury forms soil. Yet, what we characterise as archaeological sites do not appear to be “wastelands”, because they have been altered by time. Given modern threats to soil security, we are applying what we are learning from wastelands of the past to change attitudes today – we need to embrace waste, trash and rubbish as the soil of the future.
Keywords: anthropic; Belize; Maya; soil; waste